The Middle/Upper Paleolithic interface and the relationship of Neanderthals and early modern humans in the Hrvatsko Zagorje, Croatia - Karavanić, Ivor (Array, 1998)
The paper presents detailed analysis of the artefacts from levels G3 and G1 at Vindija Cave and revision of the artefacts from levels j and i at Velika Pećina. Bone points associated with Vindija G1 Neanderthals may result from imitation of or trade with early modern people. The early Upper Paleolithic in the Hrvatsko Zagorje potentially has roots in the Middle Paleolithic, from which it developed, combined with significant external influences.